Organizing A Library Tour For Students Of Pedagogical Universities - Tatyana Alekseevna Orlova; Viktoriya Eduardovna Tyan (Euro Asian Journal Publishing, 2025)
The article examines the issues of planning and conducting excursions with students of pedagogical universities. Familiarization with the libraries of the city of Tashkent and the contents of the libraries.
Keywords: Library; excursion; students